Use of Biodegradable Temporizing Matrix for Pediatric Tendoachilles Exposure: A Novel Technique in Complex Traumatic Wound Management—A Case Report - Padmalakshmi Bharathi Mohan; RaviKumar Chittoria; Shanmugapriya Ramalingam; Bharath Prakash Reddy; Kanav Gupta; Jacob Antony Chakiath (Indian Journal of Plastic Surgery)
Management of complex wounds in the pediatric population is a herculean task due to the decreased surface area available for flaps and the added scars from flap reconstruction. Biodegradable temporizing matrix (BTM) has proven useful, particularly in adult burns and complex wounds. Only a few have documented the use of BTM in complex wounds in children. A 2-year-old child presented with tendoachilles exposure of the right ankle due to a crush injury in the spokes of a motorcycle. The wound was debrided and covered with BTM. After 5 weeks, the same was delaminated, healthy granulation tissue was found covering the tendoachilles, and the raw area was grafted. BTM proved to be a versatile option for converting a complex wound to a superficial wound, and it abetted the drawbacks of a flap cover: extended hospital stay, discomfort, prolonged immobilization, and additional scars.